ASEAN economic community: Awareness and acceptance of selected member countries - Hasan, Sharina Farihah; Abdul Rashid, Khairuddin; Ahmad Sarkawi, Azila; Aripin, Srazali; Mohd Fauzi, Puteri Nur Farah Naadia (2016)
ASEAN wishes to achieve regional economic integration by 2025. Consequently, a host of policies aimed at facilitating achieving economic integration was initiated and implemented commencing 2015. However, published empirical study is scarce especially one that concerns the policies, the awareness, understanding and acceptance by the people of the ASEAN member countries. This paper attempts to patch the presence of such a gap in the literature. Specifically, this paper reports on a study to identify key policies related to the ASEAN Economic Community 2015 and assesses the ASEAN peoples’ awareness and acceptance of the identified policies. The study combined desk research with a questionnaire survey, the latter comprised of respondents carefully drawn from selected member countries of ASEAN. The results from the desk study identified the key policies that would drive ASEAN 2015 while the results from the survey suggest that on the whole the respondents are aware of ASEAN 2015, its policies and implementation. In addition, the results suggest that the ASEAN people accept the implementation of ASEAN 2015 and its corresponding policies thus, implying that they are ready and willing to call themselves citizens of a larger and regional economic community otherwise known as the ASEAN Community